Numerical Method Approaches in Optical Waveguide Modeling - Ismail, Mohd Muzafar; zainuddin, noorazlanshah (scientific.net, 2011)
Optical waveguides have been known as basic structure in integrated optics. The result of waveguide analysis is very useful to apply before fabrication process begins. In this paper, optical propagation characteristic of straight waveguide on light intensity distribution within the structures have been investigated at 1.55 micrometer waveguide. The normalized propagation constant b and effective refractive index neff conditions have been considered for the straight waveguide for single mode propagation. Both the propagation characteristic can be calculated efficiently on the personal computer by using MATLAB programming. The analysis has been analyzed using a numerical method based on finite difference method approach. The result of optimization analysis of waveguide according to the parameter study can help in practical work in designing an optical waveguide easily.